Obraz pasterzy w staropolskich kolędach i pastorałkach (na materiale tzw. „Kantyczek karmelitańskich” z XVII i XVIII wieku). Cz. II - Borejszo, Maria (Slavia Occidentalis, 2013)
This article is an attempt at reconstructing the image reflected in Old Polish Christmas carols of the activities pursued by shepherds following the news of the Saviour’s birth. The analysed material comes from the so-called “Carmelite Canticles” written in the 18th century for the Krakow female Carmelites. The research results suggest that a large part of the stories included in the Carmelite manuscripts of Christmas carols were modelled on the compositional structure of a classic Polish Christmas carol. This consisted of three elements: 1) the angels notifying the shepherds that the Saviour was born; 2) the confusion among the awoken shepherds, their preparations for leaving and the trip to Bethlehem; 3) paying homage to the Infant Jesus on arrival, presenting their gifts, shared celebrations at the manger and the shepherds’ return home. The analysed works demonstrate that the described events bear a strong Polish touch. In old Polish carols the shepherds were presented as a group of impoverished yet well-organized members of a rural society, capable of rational decisions and specific activities in unaccustomed circumstances. Special attention should be paid to the hierarchy among shepherds; it favoured the elder and best educated individuals, collective decision-making and care for all members of the shepherding community, including those less physically fit. The image of the shepherds preserved in the carols is very realistic, diversified and dynamic. Their quite detailed descriptions give an indication of how the poor lived in Polish villages of the 17th and 18th centuries and how well these communities were organized.